2021
DOI: 10.1088/1748-9326/abf7f1
|View full text |Cite
|
Sign up to set email alerts
|

Reduce aviation’s greenhouse gas emissions through immediately feasible and affordable gate electrification

Abstract: Aircraft at airport gates require power and air conditioning, provided by fossil fuel-combusting equipment, to maintain functionality and thermal comfort. We estimate the life-cycle greenhouse gas (GHG) emissions and economic implications from electrifying gate operations for 2354 commercial-traffic airports in the world. Here we show that complete electrification could yield GHG reductions of 63%–97% per gate operation relative to current practice, with greater reductions correlated with low-carbon electricit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Gate electrification will also improve air quality on the airport apron and reduce exposure to particulate pollution as well. This represents a human health benefit for the passengers, airport employees, and the general community living within proximity to the airport (Greer et al, 2021). VOCs compared to GSE (Mokalled et al, 2018).…”
Section: Findings and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gate electrification will also improve air quality on the airport apron and reduce exposure to particulate pollution as well. This represents a human health benefit for the passengers, airport employees, and the general community living within proximity to the airport (Greer et al, 2021). VOCs compared to GSE (Mokalled et al, 2018).…”
Section: Findings and Resultsmentioning
confidence: 99%
“…While investigating the same, it was seen that there are very few papers investigating this problem and most papers in aviation emission concentrates on the aircraft flying operations, essentially neglecting the contributions of the airport and ground‐based operations. In fact, the findings/results showed that out of the 11 reviewed papers, only four applied LCA methods in their analysis of environmental impacts, of which none involved LCA of APU and GSE operations in airport during aircraft turnaround time (Altuntas et al, 2014; Greer et al, 2021; Greer et al, 2023; Zampaglione de Miguel, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A more complete approach for estimating emissions would be to use a bill of materials and construction schedule from a terminal project. Effects of airport efficiency improvements on buildings (e.g., from gate electrification) would also require additional work on the tool framework ( 56 ).…”
Section: Discussionmentioning
confidence: 99%